Material Thermal Performance Comparison Between The Tomb Of Mohammad Ghaus Heritage Building And A Modern Style Dwelling In Madhya Pradesh (International Journal of Built Environment and Sustainability, 2020)
Building envelope not only provides us the protection from outside environment but also provides the necessary thermal comfort required for anyone residing inside it. It is observed that the natural cooling arrangements provided in the ancient buildings have a great influence on the thermal comfort inside the buildings. This type of arrangement of thermal comfort is not considered while designing new structures. So, the energy consumption in modern structure is more for the same thermal comfort as in ancient structures. Inside humidity, room temperature, mean surface temperatures, air variation ratio and lighting are some factors affecting thermal comfort. The materials such as cement and steel used in modern constructions are highly durable but not energy efficient. Hence necessary balance must therefore be achieved between energy efficiency and durability of modern buildings. Against this background, the paper presents a comparison of the thermal comfort inside the Tomb of Mohammad Ghaus heritage building and a modern style dwelling estimated around 10 years old. The average inside temperature of modern and heritage building was 32.65°C and 26.96°C respectively while the average outside temperature during observation period is 29.96°C. The average inside relative humidity of modern and heritage building was 61.73% and 68.93% respectively. As the heritage building was found cooler than the modern building, the study suggests that the cooling arrangement provided in the ancient buildings is imitable and beneficial to be incorporated in modern buildings
Keywords: Thermal comfort; Ancient and Modern Building; Air temperature; Air velocity; Thermal Simulation